(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Pseudomonas aeruginosa is a major clinical microbiological problem affecting the hospitalized and non-hospitalized patients throughout the world. The susceptibility patterns of P. aeruginosa vary geographically and with clinical presentation. Pseudomonas can rapidly develop resistance especially when single drug is employed due to frequent mutation and its own innate mechanisms of antibiotic resistance. Objectives: This cross sectional study was carried out to determine in-vitro resistance pattern of Pseudomonas isolates to common antimicrobial agents by disc diffusion method. Various clinical samples were collected from Combined Military Hospital (CMH), Dhaka. Materials and Methods: This study was carried out in the Department of Microbiology, Armed Forces Institute of Pathology (AFIP) from 01 March 2012 to 31 August 2012. Identification and antibiogram were performed for Pseudomonas isolates following standard microbiological laboratory procedure. Results: A total of 198 P. aeruginosa were isolated from the various specimens. The highest number (76) of P. aeruginosa were isolated from wound swab/pus (38.38%), followed by urine (56, 28.28%), bronchial wash (23, 11.62%). In present study, maximum number of P. aeruginosa are resistant to penicillin (98.98%) followed by cephalosporins (89.85%), aminoglycosides (80.04%), carbapenems (76.08%). The most sensitive antibiotic was combination of piperacillin and tazobactam (only 3.37% resistant) followed by ciprofloxacin (54.04%) and azithromycin (59.18%). Conclusion: To prevent the spread of the resistant bacteria, it is critically important to have strict antibiotic policies. The surveillance programmes for multidrug resistant organisms and infection control procedures need to be implemented properly. The antibiotic susceptibility pattern of P. aeruginosa needs to be continuously monitored in specialized clinical units and the results readily made available to the clinicians so as to minimize the resistance. Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 45-49